Cidadelas da Cultura no Lazer: Um estudo de antropologia da imagem do SESC São Paulo - Dines, Yara Schreiber (2007)
Leisure and culture are subjects that have gained a growing relevance in contemporary society in light of the changes resulting from the restructuring of the productive process on a global scale, thus raising a series of questions and reflections regarding leisure practices, their meaning and their social significance. The present work is focused on leisure in São Paulo city, in an attempt to grasp the meanings which this concept and that of culture have come to take on in this metropolitan context during the last decades of the 20th century. This was the period when leisure was consolidated as a field of studies associated with the sphere of labor and new demands for entertainment in the city, thus reinforcing the need to understand the various meanings it came to acquire. The thesis is centered on an institution designed to provide leisure for workers - the São Paulo Commerce Social Service, SESC - and it analyses the guidelines that have oriented its course of action and the social practices it has been implementing since it was created in the 40's. The research was based on the iconographic collection of the SESC São Paulo and interviews with members and former workers of the institution, thus allowing for the analysis of the iconography to be set in proper context. This methodology unveiled the significance of the various practices of sport and culture developed by the institution along its 60 years of existence, thus permitting us the identify some aspects of the guiding lines followed by the SESC São Paulo, and to reflect upon the meanings taken on by leisure and culture within this universe, in the dialogue it has established with the metropolis